Comparative Analysis of Compressive Strength of Natural and Brick Aggregate Concrete - Khadka, Ankit; Timisina, Paribesh; Adhikari, Sundar (Journal of UTEC Engineering Management, 2025)
An experimental study had been conducted to study of substituting natural coarse aggregate with different proportions of crushed brick aggregate impacts the compressive strength of concrete. The study aims to compare the compressive strength of nominal mixed M15, M20 and M25 grade concrete by replacing stone aggregate with crushed bricks aggregate with volumetric replacement (0%,25%,50%,75% and 100%) also find the relation between the results of NDT and destructive test. A total of 45 number of concrete mixes specimens are casted with and without crushed bricks. These specimens were tested at 28 days for compressive strength. In this paper experimental research has been carried out involving both destructive with universal testing machine and non-destructive test with rebound hammer test. The result indicated that using crushed bricks reduces the strength of concrete. The research emphasizes reusing bricks which reduces waste and enhance recourse recycling and conservation.